Factors Influencing Gen-Z Consumer Loyalty Towards Mobile Service Provider (MSP) In Indonesia - Khairulah, Yusuf Akbar; Rachmawati, Indira (eProceedings of Management, 2023)
Mobile Service Provider is a company that offers transmission services to users of wireless devices. As Gen Z is thegeneration that grew up and spent their lives assisted by technology, it has become a huge part of their lives as usersof mobile service providers. The aim / objectives of this study are to examine the attitudes and beliefs of the gen Ztowards MSP’s. The phenomena in this study were explored using quantitative methods. This research received 402responses. The variables used in this research are: Performance/Quality Value, Price/Value for Money, EmotionalValue, Relational Value, and Customization Value, Customer Satisfaction, Switching Cost, and AlternativeAttractiveness. This research uses the non-probability sampling method quota sampling. The results of this studyshows that perceived values do affect satisfaction positively, and also, from the research, it can be said that satisfactionand loyalty are mediated and moderated by and through both alternative attractiveness and switching cost. Thesuggestions for future research are to develop the research results found in this study so further research can becarried out, and if possible, add more factors which impact satisfaction and loyalty aside those used in this research.Keywords-customer satisfaction, customer loyalty, switching cost, alternative attractiveness, Gen Z.